Analysis of Success Factors of Koperasi Peternakan Bandung Selatan (KPBS) Pangalengan - Fadli Rahmat, Muhammad; Wisesa, Anggara (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. Cooperative is an economic organization of free people who join together to improve prosperity through service to its members as owners and users, on the basis of equality, self-help, and mutual cooperation. The purpose of cooperative is to promote the prosperity of members in particular and society in general, and also to build the national economic system, in order to realize a progressive, just and prosperous society based on Pancasila and the 1945 Constitution. Unfortunately, in 2016, government dissolved 61 thousand cooperatives in the entire of Indonesia. While in 2017, 40,013 units of cooperatives was dissolved. One of the quite successful cooperatives in Bandung is the Koperasi Peternakan Bandung Selatan or KPBS Pangalengan. The success of cooperatives is influenced by several factors, those are member participation, professionalism of management, and external factors. This research conducted by using a qualitative rapid-ethnography method, gather the data from 9 respondents with different role in KPBS Pangalengan by using the semi-structured interview. The result analyzes use spradley method based on the interview result. The result has shown that the success of KPBS Pangalengan determined member participation, professionalism of management, and the external factor through increasing the price of milk, increasing the productiveness of cooperatives, and using the facilities that provided by the cooperative.Keywords: Cooperative, Success Factor of Cooperative, Success Cooperative, KPBS